1994
DOI: 10.3109/00365519409085464
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine and thiol compound fractions after oral administration of N-acetylcysteine

Abstract: The total concentration of the atherogenic aminothiol acid homocysteine in plasma of healthy volunteers was decreased after oral administration of N-acetylcysteine (NAC), whereas the reduced and free (non-protein bound) fractions of homocysteine were increased. The decrease of the total fraction varied between 20 and 50% and was dose-related. Cysteinylglycine was also decreased after the administration of NAC, whereas cysteine did not change. Administration of high amounts of NAC probably displaces homocystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 20 publications
3
42
1
2
Order By: Relevance
“…In humans, about 75% of plasma homocysteine is bound to protein through disulfide bonds with cysteine residues of plasma proteins and the remainder exists mainly in the forms of lowmolecular-weight disulfides such as homocystine and homocysteine-cysteine (49). The plasma low-molecular-weight homocysteine is thought to be metabolized in the kidney (45). The present study demonstrated that methionine supplementation significantly increased both plasma protein-bound and non-protein-bound homocysteine concentrations and these increases were significantly suppressed in rats fed the 40% casein diet compared with rats fed the 10% casein diet.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In humans, about 75% of plasma homocysteine is bound to protein through disulfide bonds with cysteine residues of plasma proteins and the remainder exists mainly in the forms of lowmolecular-weight disulfides such as homocystine and homocysteine-cysteine (49). The plasma low-molecular-weight homocysteine is thought to be metabolized in the kidney (45). The present study demonstrated that methionine supplementation significantly increased both plasma protein-bound and non-protein-bound homocysteine concentrations and these increases were significantly suppressed in rats fed the 40% casein diet compared with rats fed the 10% casein diet.…”
Section: Discussionsupporting
confidence: 49%
“…It has been shown that N-acetylcysteine (45) or cystine (46) had a hypohomocysteinemic effect in humans. Hultberg et al (45) provided a view that administration of N-acetylcysteine might increase plasma N-acetylcysteine concentration and thereby stimulate the displacement of homocysteine from the protein-binding site, leading to increased clearance of non-protein-bound homocysteine in the kidney. Therefore, the possibility that the effect of dietary protein level on plasma homocysteine concentration is associated, at least in part, with cyst(e)ine intake or plasma cysteine concentration cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…3,19) In contrast, dietary addition of cysteine did not decrease, but rather increased, the plasma homocysteine concentration in the present study. The reason for the discrepancy between the results of previous studies and the results of this one appears at least in part to be different experimental conditions, e.g., the addition level and administration method of methionine and cysteine.…”
Section: )contrasting
confidence: 52%
“…Cysteine competes with homocysteine for transporters in several tissues 18) and for the homocysteine-binding site of plasma albumin. 19) Thus, the possibility that the increase in the plasma cysteine concentration is partly associated with the effects of glycine, serine, histidine, and arginine cannot be excluded, although the causal relationship is still unclear.…”
Section: )mentioning
confidence: 99%
“…In humans, about 75% of plasma homocysteine is bound to protein through disulfide bonds with cysteine residues of plasma proteins, especially albumin, and the remainder exists mainly in the forms of low-molecular-weight disulfides such as homocystine and homocysteine-cysteine (34). Hultberg et al (15) demonstrated that the plasma total homocysteine concentration in healthy humans was decreased after single oral administration of NAC, whereas non-protein-bound homocysteine concentration was increased. Based on these results, they postulated that administration of NAC (or cysteine) might displace homocysteine from its protein-binding site by disulfide exchange reaction and lead to the formation of mixed low-molecular-weight cysteine and NAC disulfides with high rate of renal clearance and an increased metabolic bioavailability, thereby eliminating homocysteine from plasma.…”
Section: Discussionmentioning
confidence: 99%